2011
DOI: 10.1007/s00170-011-3195-8
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical changes during composite milling: recurrence and multiscale entropy analysis

Abstract: Fluctuations describing chatter in the milling process of a composite material were analyzed using statistical, recurrence, and multiscaled entropy analyses. Through changing the rotational speed, we observed the appearance of chatter vibrations and signatures of intermittency. The corresponding characteristic change of recurrences could be used to invent a new efficient control procedure of milling. The workpiece was prepared from nonuniform material based on epoxy-polymer matrix composite reinforced by carbo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 29 publications
0
42
0
Order By: Relevance
“…The MSE has been successfully applied to different research fields in the past decades. These applications include the analyses of the human gait dynamics [2], heart rate variability [3,4], electroencephalogram [5], postural control [6], vibration of rotary machine [7,8], rainfall time series [9], time series of river flow [10], electroseismic time series [11], time series of traffic flow [12], social dynamics [13], chatter in the milling process [14], and vibrations of a vehicle [15], etc.. These works demonstrate the effectiveness of the MSE algorithm for the analysis of the complex time series.…”
Section: Introductionmentioning
confidence: 99%
“…The MSE has been successfully applied to different research fields in the past decades. These applications include the analyses of the human gait dynamics [2], heart rate variability [3,4], electroencephalogram [5], postural control [6], vibration of rotary machine [7,8], rainfall time series [9], time series of river flow [10], electroseismic time series [11], time series of traffic flow [12], social dynamics [13], chatter in the milling process [14], and vibrations of a vehicle [15], etc.. These works demonstrate the effectiveness of the MSE algorithm for the analysis of the complex time series.…”
Section: Introductionmentioning
confidence: 99%
“…Davim et al [4] studied the machining aspects of milling on medium density fibre boards and reported that feed and speed have more influence on surface roughness. Litak et al [5] performed a multi scale entropy analysis on carbon fibre reinforced composites. Rentsch et al [6] performed finite element modeling on cutting of carbon fibre reinforced plastics with a disc milling cutter and reported that the calculated and experimental results of the material removal mechanism were almost the same but the cutting forces in comparison with experimental data were not satisfactory.…”
Section: Literature Surveymentioning
confidence: 99%
“…The recurrence quantification analysis can provide useful information even for short and non-stationary data, where other methods fail. The RQA can be applied for various kinds of data to recognize dynamical behaviour [23]. Here the RQA is also applied to investigate milling process instability.…”
Section: Theory Of Recurrence Analysismentioning
confidence: 99%
“…Although, experimental results are very often compared with FEM results [3,17], the problem of experimental signal analysis remains an open question. Different methods of signal analysis are applied in order to recognize chatter vibrations in cutting operations, including multifractal and wavelet approaches [38], multiscale entropy [23] HilbertHuang transform [20], recurrence analysis [22], flicker-noise spectroscopy [21] and audio signal analysis [32]. As it was mentioned before, the HSM method is also applied to thin-walled aluminium components for the aircraft industry to increase productivity [8].…”
Section: Introductionmentioning
confidence: 99%